Embodied interaction and immersive film experiences on smartphones - (:unkn) unknown (Palgrave Macmillan, 2021)
This study introduces the components of what connects, but, at the same time, distances smartphone spectatorship from stationary screen-based viewing. On one hand, these include the multisensory nature of spectatorship that involves vision, sound, touch, and kinesthetic engagement. On the other, a viewer’s embodied involvement affords a specific form of interactive film experiences. Exploring multisensory and embodied viewing, the goal of this study is to reflect on audiovisual storytelling and story-receiving on smartphones. This distinction is key: while a moving-image narration may be loyal to cinematic formulae, smartphone viewing involves spontaneous customizations, where narrative experiences become defined by one’s individual choices and bodily engagement. The study presents the mechanisms of story-receiving through multisensory and 360-degree narrative film experiences on smartphones.
Mobile Storytelling in an Age of Smartphones
Keywords: Spectatorship; Embodiment; Immersive Media; Creative Arts Practice; Creative Technologies; Digital Engagement; 360 video; Embodiment; Narrative theory; Spectatorship; smartphone